Pandora's box opened : an examination and defense of historical-critical method and its master practitioners - Harrisville, Roy A. (2014)
For many, the historical-critical method has released a host of threats to Christian faith and confession. In Pandora's Box Opened, however, Roy Harrisville argues that despite the evils brought upon biblical interpretation by the historical-critical method, there is still hope for it as a discipline. Harrisville begins by describing the emergence and use of the historical-critical method. He then attends to the malaise that has come over the method, which he says still persists. Finally, Harrisville commends the historical-critical method, though shorn of its arrogance. He claims that the method and all its users comprise a "Pandora's Box" that, when opened, releases "a myriad other pains," but hope still remains.
Ancient thumbnail history. Hermes and Homer ; Halakhah and Haggadah ; Alexandria and Antioch ; Cassian and Augustine -- The Reformation era. Martin Luther ; John Calvin ; Thomas Muntzer -- Orthodoxy and pietism. Matthias Flacius Illyricus ; Johann Albrecht Bengel -- The enlightenment. Baruch Spinoza ; John Locke ; Christian Wolff ; Sigmund Jacob Baumgarten -- COntemporary in dissent : Johann Georg Hamann. Postscript : Johann Christian Edelmann -- The modern period. Johann Salomo Semler ; Friedrich Schleiermacher ; The Strauss-Baur school ; Georg Heinrich August Ewald ; The Americans -- The twentieth century. Karl Barth ; Rudolf Bultmann ; Chicago, Harvard, Yale, Union, Princeton -- Summing Up -- The malaise. The attacks ; Alternatives ; The current situation -- The historical-critical method down to size. On limits ; On objectivity ; On the neutral observer ; On the community ; On the text ; On the author ; On the right to criticism -- A last word.
Includes bibliographical references and indexes.
Keywords: Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc. -- History